Penerapan Teori Taksonomi Bloom Dalam Meningkatkan Kemampuan Kognitif Siswa Pada Pembelajaran Digital Di Sma Bakti Ponorongo - Alfiyatul Faizah; Alif Dani Amrullah; Alifah Sofwatun Nisa'; Aliya Husna Amanda Putri; Annisa Maghfiratul Khasanah; Annisa Nur Fitriani; Nurul Malikah (https://ejournal.insuriponorogo.ac.id/, 2024)
This research aims to explore the application of Bloom's Taxonomy theory in improving students' cognitive abilities in digital learning at Bakti Ponorogo High School. With a qualitative-descriptive approach, this research involves observation, interviews, and documentation analysis to evaluate how teachers design digital learning tools that are structured based on the six levels of Bloom's Taxonomy: remembering, understanding, applying, analyzing, evaluating, and creating. The research results show that the application of Bloom's Taxonomy effectively helps students develop critical, analytical and creative thinking skills. Teachers are able to design learning activities that utilize digital technology, such as interactive modules, simulations and digital-based projects, which encourage active student involvement. However, challenges such as students' reliance on artificial intelligence (AI) to complete assignments and lack of supervision of technology use are significant obstacles. To overcome these challenges, strategies are needed such as training for teachers in designing tasks that promote independent thinking, as well as the ethical integration of technology use in the learning process. This research confirms the importance of applying Bloom's Taxonomy in digital learning to support the development of students' cognitive abilities in the technological era.